STRATEGI SUPERVISI AKADEMIK YANG MEMPENGARUHI MUTU PEMBELAJARAN - Istiqomah Eka Diyanti; Ayuningrum; Erwin Salpa Riansi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Supervision plays an important role in improving the overall quality of education. effective supervision not only focuses on oversight but also on professional development for educators. With the right approach, supervision can become a powerful tool to improve the quality of learning in elementary schools. (SD). This research uses a qualitative method in the form of a literature review that analyzes various references related to Supervision Strategies that Affect the Quality of Learning. The purpose of academic supervision is to improve the quality of the learning process, among other things, by providing feedback, guidance, and developing teachers' abilities so that their competencies increase. Academic supervision is conducted with the intention of helping teachers develop their professional capabilities in understanding academics, classroom life, enhancing their teaching skills, and utilizing their abilities through certain techniques. This research emphasizes that supervision—both from the principal and supervisors—is an important factor in improving teacher performance.Effective supervision strategies must be designed systematically and planned to encourage the improvement of teaching quality, teacher professionalism, and student learning outcomes. By implementing the right supervision strategies, schools can create an effective, innovative, and sustainable learning culture, thereby positively impacting the overall quality of education.